178. Comparing the Incidence of Multidrug Resistant Bacteremia, Fungemia and Hospital-acquired Clostridioides difficile Infection in COVID-19 Versus Non-COVID-19 Patients: a Single Hospital, One-year Observational Study in New York City. (4th December 2021) - Chiu, Chia-Yu; Sarwal, Amara; Widjaja, Michael; Feinstein, Addi
Abstract: This abstract has been withdrawn.